PENGARUH PEMBERIAN REBUSAN AIR JAHE TERHADAP LOW BACK PAIN PADA PEKERJA PEMBUAT BATU BATA - Ika Nur Saputri; Irma Nurianti; M. Riduwan (JURNAL KESMAS DAN GIZI (JKG), 2021)
Low Back Painis a musculoskeletal disorder which located at the lower-back, is caused by several of diseases and many of bad activities of the body. One of the non-pharmacological therapies that can be used in reducing the low back pain’ssuffer of the patients is ginger water. This research aimisto find out the effect of ginger waterto decrease pain intensity in the low back pain patient. This researchis pre-experimentalwith the design of the pre-testand post-test one group design.The research design used a research design with a quasi-experimental or quasi-experimental approach. The population in this study were 35 workers who made bricks and sample taken using a total sampling that was 35workers. Data collection methods were primary data and secondary data. The data analysis used was univariate analysis and bivariate analysis. The results showed the p value = 0.000, with a degree of error (?) = 5%, p value <0.05, which means that there is an effect of giving boiled ginger water on low back pain in brick-making workers in Beringin District in 2021. The conclusion shows that there is an effect of giving boiled ginger water on low back pain in brick-making workers in Beringin District in 2021. It is suggested that brick workers can make ginger boiled water as a method to reduce complaints of low back pain.